2021
DOI: 10.1080/0886022x.2021.1979039
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemia is an independent risk factor for AKI among hospitalized patients with COVID-19 infection

Abstract: Background: This study sought to investigate incidence and risk factors for acute kidney injury (AKI) in hospitalized COVID-19. Methods: In this retrospective study, we enrolled 823 COVID-19 patients with at least two evaluations of renal function during hospitalization from four hospitals in Wuhan, China between February 2020 and April 2020. Clinical and laboratory parameters at the time of admission and follow-up data were recorded. Systemic renal tubular dysfunction was evaluated via 24-h urine collections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
11

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 45 publications
0
15
0
11
Order By: Relevance
“…Chen et al reported that hypophosphatemia is an independent risk factor for acute kidney injury (AKI). They also indicated that renal tubular dysfunction might be the cause of renal phosphate loss [26].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al reported that hypophosphatemia is an independent risk factor for acute kidney injury (AKI). They also indicated that renal tubular dysfunction might be the cause of renal phosphate loss [26].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…They postulated that this finding might be explained by severe malnutrition in ESRD patients with COVID-19 [28]. Other suggested mechanisms associated hypophosphatemia with renal dysfunction [26]. AKI may follow the course of COVID-19 through several mechanisms [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al. found that in hospitalized COVID-19 patients, a higher level of serum phosphorus was associated with an increased risk of AKI [ 46 ]. Further research on the molecular biology mechanism is helpful in exploring the potential relationship between COVID-19 infection and AKI.…”
Section: Discussionmentioning
confidence: 99%